Tanggung Jawab Pengelola E-Warong atas Selisih Jumlah Barang Perspektif Sayyid Sabiq di Kelurahan Simulajadi, Tanjung Balai - Nurhayana Khofifah Adisty Sagala; Sahliah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The research sheds light on the implementation issues of the Non-Cash Food Assistance Program (BPNT), particularly the E-Warong program in Simulajadi Tanjung Balai Sub-District. It aims to understand the management practices of E-Warong and the background of discrepancies in the quantity of goods received by the community. The study concludes that the discrepancy between the quantity of goods and their corresponding value received by the community does not align with the funds allocated by the government, indicating discrepancies attributed to fraudulent practices by shop owners. This juridical-empirical study employs a living case studies approach followed by conceptual and statute approaches. Data collected through interviews and document analysis reveal discrepancies in the distribution of staple goods among BPNT recipients in Simulajadi Tanjungbalai.